Prevalence of Postural Abnormalities of Spine and Shoulder Girdle in Sanda Professionals - Hamed Babagoltabar Samakoush; Aliasghar Norasteh (The Society of Aging and Physical Activity (SAPA), 2017)
Background. Performing skilful movement patterns during sport practice sessions and real competition can cause negative adaptations in the musculoskeletal system. Objectives. The aim of this study was to investigate the incidence of postural abnormalities of the spine and shoulder girdle among professionals practising Sanda in Mazandaran province. Methods. Forty professional Sanda athletes participated in this study. The photogrammetric technique was used to record and measure the angle of forward head and forward shoulder. A flexible ruler was used to measure the angle of kyphosis and lordosis. Results. Based on the findings, the prevalence of abnormalities in the athletes was respectively: 75% forward head, 80% forward shoulder, 85% kyphosis and 65% lordosis. Also, the average angles in athletes included: kyphosis 47±4.63, lordosis 47.40±7.18, forward head 48.02±2.15 and forward shoulder 54.12±2.05 degrees. Conclusion. Based on the results, it appears that professional Sanda athletes have exposure to alterations in shoulder and spine position, thanks to the sporting condition and type of exercises. Of course, further studies should be performed with large samples to obtain confirmed results. However, coaches and athletes should consider special corrective exercise programmes and perform them to prevent such abnormalities.